2019
DOI: 10.1136/bjsports-2019-100957
|View full text |Cite
|
Sign up to set email alerts
|

ICON PART-T 2019–International Scientific Tendinopathy Symposium Consensus: recommended standards for reporting participant characteristics in tendinopathy research (PART-T)

Abstract: We aimed to establish consensus for reporting recommendations relating to participant characteristics in tendon research. A scoping literature review of tendinopathy studies (Achilles, patellar, hamstring, gluteal and elbow) was followed by an online survey and face-to-face consensus meeting with expert healthcare professionals (HCPs) at the International Scientific Tendon Symposium, Groningen 2018. We reviewed 263 papers to form statements for consensus and invited 30 HCPs from different disciplines and geogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 15 publications
0
59
0
Order By: Relevance
“…47 A further ICON consensus statement highlighted that patient characteristics relating to general health may be a major confounder to treatment outcomes in tendinopathy. 48 Patients with chronic tendinopathy, especially older and more sedentary individuals, often have associated comorbidities, for example, diabetes, 49 high cholesterol 50 and high body mass index. 51 These characteristics are not routinely measured in tendinopathy studies, but it is recommended that they are reported in future clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…47 A further ICON consensus statement highlighted that patient characteristics relating to general health may be a major confounder to treatment outcomes in tendinopathy. 48 Patients with chronic tendinopathy, especially older and more sedentary individuals, often have associated comorbidities, for example, diabetes, 49 high cholesterol 50 and high body mass index. 51 These characteristics are not routinely measured in tendinopathy studies, but it is recommended that they are reported in future clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…These candidate domains were then considered for their importance as core health-related domains in tendinopathy, first by online survey (stage 2, August 2018) and then at an in-person meeting at the 2018 International Scientific Tendinopathy Symposium (ISTS, Groningen, the Netherlands) (stage 3, September 2018). The consensus process described here was one of three separate projects discussed at the ISTS consensus meeting; the other two dealt with terminology10 and reporting of participant characteristics 11…”
Section: Methodsmentioning
confidence: 99%
“…The outcome measures were designed and registered prior to the publication of a recent consensus on outcome measures [36]. There were no changes to outcome measures after registration of the protocol at ISCRTN, although we did alter the ultrasound analysis from what was described in our ethics protocol by focusing on tendon thickness rather than echo texture.…”
Section: Outcome Measuresmentioning
confidence: 99%